Słownik asocjacyjny jako narzędzie przygotowania komentarza lingwokulturologicznego - Orzechowska, Joanna (Acta Polono-Ruthenica, 2018)
A person who learns a foreign language should get acquainted with associations of the studied words since they belong to the (passive or active) lexicon of the representatives of the culture of the studied language. Word associations which are stored in the memory (consciousness) of every representative of any language and culture are registered in the dictionary of associations as an associative norm. Learners of Russian are able to get to know such associations through mini-texts appropriately chosen by their teachers (poems, songs, riddles, fixed expressions, proverbs). Such texts constitute a linguistic-culturological commentary which allows learners to “immerse” themselves in the Russian reality and culture, which is the main assumption of any teacher of Russian as a foreign language who adheres to the trend of applied linguistics and culturology. Classes when the described commentary is used help students to develop their socio-cultural competence, which in turn should prevent a cultural conflict during intercultural communication. It seems that in the next decade the attention of teacher trainers will be focused on this aspect of teaching.